Prosedur Tindakan Percutaneous Coronary Interventional dengan kasus Chronik Total Occlusion Pada Arteri Koroner - Astuti Juniarti Daing; Kusman Kusman (Jurnal Ventilator, 2023)
Percutaneous coronary interventional (PCI) is a minimally invasive blood vessel widening procedure using balloons and stents, the PCI procedure in CTO cases uses the double puncture technique and the C-arm tube angle position LAO 45 ? - Cranial 15 ? and Frontal 0 ? - Cranial 30 ?. The aim of using the double puncture technique is to see the entry point and exit point of chronic total occlusion. This study aims to find out the latest literature related to PCI procedures in CTO cases, including current developments and status. This research is a literature review (Summary Method) where literature exploration is carried out using various sources with the keyword "Percutaneous Coronary Interventional (PCI) Chronic Total Occlusion (CTO)". Reference sources used in preparing this article include books, as well as articles in scientific journals in English and Indonesian. Based on the results of a review of several literature procedures, PCI procedures with CTO cases consist of patient preparation, preparation of tools and materials, and examination techniques for selecting puncture access. radial artery and femoral artery, patient position, C-arm angle position. There is a role for radiographers that conforms to SKKNI radiographer Number 237 of 2020, and the role of radiographers in the actions taking place in the cathlab is to prepare the readiness of the C-arm aircraft and pay attention to radiation protection during the action.